Superior Outcomes and Reduced Wait Times in Pediatric Recipients of Living Donor Liver Transplantation - Kehar, Mohit (Transplant Direct, 2019)
BACKGROUND: Living donor liver transplantation (LDLT) is increasingly used to bridge the gap between the current supply and demand imbalance for deceased donor organs to provide lifesaving liver transplantation. METHODS: Outcomes of 135 children who underwent LDLT were compared with 158 recipients of deceased donor liver transplantation (DDLT) at the largest pediatric liver transplant program in Canada. RESULTS: Recipients of LDLT were significantly younger than deceased donor recipients (P ≤ 0.001), less likely to require dialysis pretransplant (P < 0.002) and had shorter wait time duration when the primary indication was cholestatic liver disease (P = 0.003). The LDLT donors were either related genetically or emotionally (79%), or unrelated (21%) to the pediatric recipients. One-, 5-, and 10-year patient survival rates were significantly higher in LDLT (97%, 94%, and 94%) compared with DDLT (92%, 87%, and 80%; log-rank P = 0.02) recipients, as were graft survival rates (96%, 93%, and 93% for LDLT versus 89%, 81.4%, and 70%, respectively, for DDLT; log-rank P = 0.001). Medical and surgical complications were not statistically different between groups. Graft failure was higher in recipients of DDLT (odds ratio, 2.60; 95% confidence interval, 1.02, 6.58) than in the LDLT group after adjustment for clinical characteristics and propensity score. CONCLUSIONS: Living donor liver transplantation provides superior outcomes for children and is an excellent and effective strategy to increase the chances of receiving a liver transplant.